2012
DOI: 10.1242/dev.080259
|View full text |Cite
|
Sign up to set email alerts
|

Dual role for Insulin/TOR signaling in the control of hematopoietic progenitor maintenance in Drosophila

Abstract: The interconnected Insulin/IGF signaling (IlS) and Target of Rapamycin (TOR) signaling pathways constitute the main branches of the nutrient-sensing system that couples growth to nutritional conditions in Drosophila. Here, we addressed the influence of these pathways and of diet restriction on the balance between the maintenance of multipotent hematopoietic progenitors and their differentiation in the Drosophila lymph gland. In this larval hematopoietic organ, a pool of stem-like progenitor blood cells (prohem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 33 publications
4
120
0
Order By: Relevance
“…S9). PSC-specific overexpression of Pten, an inhibitor of insulin signaling causes a reduced niche and reduced differentiation (22). We observed that overexpression of ARF1 alone in the niche (PCol85Gal4GFP/UASarf1) does not affect niche cell number (Fig.…”
Section: Perturbation Of Arf1 and Its Activated Form Leads To Aberranmentioning
confidence: 69%
See 2 more Smart Citations
“…S9). PSC-specific overexpression of Pten, an inhibitor of insulin signaling causes a reduced niche and reduced differentiation (22). We observed that overexpression of ARF1 alone in the niche (PCol85Gal4GFP/UASarf1) does not affect niche cell number (Fig.…”
Section: Perturbation Of Arf1 and Its Activated Form Leads To Aberranmentioning
confidence: 69%
“…For example, sumoylation defective mutants like Ubc9 show posterior lymph gland tissue overgrowth (31). Pten mutants also display secondary lymph gland lobe overgrowth with numerous proliferating cells (22). Even in asrij-depleted posterior lobes stemness is lost and cells differentiate (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was thus proposed that the PSC provides a microenvironment that supports hematopoietic progenitor maintenance in the LG (10,11). In line with this model, increasing or decreasing PSC size/activity can, respectively, impede or promote hemocyte differentiation (11,(13)(14)(15)(16)(17)(18)(19). However, differentiated hemocytes are frequently observed close to the PSC, and it is unclear how progenitor fate is maintained in the posterior lobes, which are far apart and physically separated from the PSC.…”
mentioning
confidence: 99%
“…In Drosophila, neural-producing Dilps cell-autonomously regulate male GSC division at the G2 phase, as well as GSC and hematopoietic progenitor maintenance [17][18][19]. They also non-cell autonomously control midgut intestinal stem cell proliferation [20].…”
mentioning
confidence: 99%